2022
DOI: 10.1007/s10798-022-09772-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender does not make the difference: interest in STEM by gender is fully mediated by technical socialization and degree program

Abstract: In Germany, there is a shortage of skilled workers in the fields of science, technology, engineering, and mathematics (STEM) and especially in technology with declining interest in technology and with supposedly fewer teachers in technology education in the next 20 years. The present study examined whether students’ interest in STEM is dependent on their career choices (i.e., their degree program), their technical socialization, their personality, and gender. A survey in Germany, Baden-Wuerttemberg ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Focus Areas References Conducting research on strategies and initiatives to promote gender parity in the STEM sector (Benavent et al, 2020), (García-Holgado et al, 2020), (Gweshe & Chiware, 2023), (Reinking & Martin, 2018), (Rushton & King, 2020) Interventions targeting the modification of female students' perspectives on STEM jobs (Dönmez, 2023) Conducting a study on the differences in confidence, interest, and goals across genders in the STEM fields, and investigating how cultural and societal expectations impact women's participation in STEM (Chan, 2022) Adapting formal and extracurricular educational programs and STEM courses to attract more genders. Adapting programs to boost female STEM enrollment in specific contexts is crucial (Friedman-Sokuler & Justman, 2020), (Goreth & Vollmer, 2023), (Levine et al, 2015), (Price et al, 2019), (Sangar, 2022), (Schilling & Pinnell, 2018), http://ijlter.org/index.php/ijlter (Sevilla et al, 2023) Analyzing the influence of STEM educational programs on students' attitudes (Van Wassenaer et al, 2023) Conducting research on particular policies that have a strong likelihood of reducing obstacles encountered by women in the field of science (Greider et al, 2019) Creating and evaluating virtual STEM laboratories with the aim of engaging female students (Vergara, 2023) Conducting research on the emotional components of learning and students' attitudes toward STEM subjects (Pelch, 2018), (Zhou et al, 2019) Examining the factors contributing to disparities in gender representation in STEM fields (Delaney & Devereux, 2019), (Naukkarinen & Bairoh, 2020) Examining the impact of gender and nationality on the experiences of women in STEM fields (Lim et al, 2021) Conducting research on women's cognitive abilities, interests, beliefs, motivation, engagement, advantages, and challenges in STEM fields (Chiang et al, 2023),…”
Section: Key Research Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus Areas References Conducting research on strategies and initiatives to promote gender parity in the STEM sector (Benavent et al, 2020), (García-Holgado et al, 2020), (Gweshe & Chiware, 2023), (Reinking & Martin, 2018), (Rushton & King, 2020) Interventions targeting the modification of female students' perspectives on STEM jobs (Dönmez, 2023) Conducting a study on the differences in confidence, interest, and goals across genders in the STEM fields, and investigating how cultural and societal expectations impact women's participation in STEM (Chan, 2022) Adapting formal and extracurricular educational programs and STEM courses to attract more genders. Adapting programs to boost female STEM enrollment in specific contexts is crucial (Friedman-Sokuler & Justman, 2020), (Goreth & Vollmer, 2023), (Levine et al, 2015), (Price et al, 2019), (Sangar, 2022), (Schilling & Pinnell, 2018), http://ijlter.org/index.php/ijlter (Sevilla et al, 2023) Analyzing the influence of STEM educational programs on students' attitudes (Van Wassenaer et al, 2023) Conducting research on particular policies that have a strong likelihood of reducing obstacles encountered by women in the field of science (Greider et al, 2019) Creating and evaluating virtual STEM laboratories with the aim of engaging female students (Vergara, 2023) Conducting research on the emotional components of learning and students' attitudes toward STEM subjects (Pelch, 2018), (Zhou et al, 2019) Examining the factors contributing to disparities in gender representation in STEM fields (Delaney & Devereux, 2019), (Naukkarinen & Bairoh, 2020) Examining the impact of gender and nationality on the experiences of women in STEM fields (Lim et al, 2021) Conducting research on women's cognitive abilities, interests, beliefs, motivation, engagement, advantages, and challenges in STEM fields (Chiang et al, 2023),…”
Section: Key Research Issuesmentioning
confidence: 99%
“…(Daniela et al, 2022) Researchers globally have shown a significant amount of interest in the research fields presented in Table 1. These areas are an examination of flexible teaching programs, including both formal and extracurricular ones, as well as STEM classes with the goal of promoting gender diversity (Friedman-Sokuler & Justman, 2020; Goreth & Vollmer, 2023;Levine et al, 2015;Price et al, 2019;Sangar, 2022;Schilling & Pinnell, 2018;Sevilla et al, 2023) and emphasising the significance of making program modifications in order to increase the number of women who participate in STEM fields while taking into account certain contextual factors (Friedman-Sokuler & Justman, 2020;Goreth & Vollmer, 2023;Levine et al, 2015;Price et al, 2019;Sangar, 2022;Schilling & Pinnell, 2018;Sevilla et al, 2023).…”
Section: Key Research Issuesmentioning
confidence: 99%